RED GINGER BOILED COMPRESSES ARE MORE EFFECTIVE IN REDUCING THE PAIN SCALE IN RHEUMATOID ARTHRITIS THAN CITRONELLA BOILED WATER COMPRESSES - Novika Andora; aulia rahman (Jurnal Vokasi Keperawatan (JVK), 2021)
The citronella plant contains analgesic compounds that help relieve aches or pains such as muscle aches and joint pain, pegalinu due to rheumatoid arthritis or anti-rheumatism. In addition, it is also useful as an antioxidant that can prevent cancer, in lemongrass there are anti-microbial and anti-bacterial substances that are useful as infection drugs. Red ginger compress is a combination of warm therapy and relaxation therapy that is useful for people with joint pain that has no side effects. Ginger contains phenolic compounds which have been shown to have anti-inflammatory effects and are known to be effective in relieving joint disease and muscle tension so that it can improve the declining musculoskeletal system. In addition, ginger also has a pharmacological effect, namely a hot and spicy taste where this heat can relieve pain, stiffness and muscle spasms and the occurrence of vasodilation of blood vessels. Simpur Health Center Bandar Lampung the incidence of rheumatoid arthritis increased in 2019 from 262 to 284 people. The purpose of this study was to determine the difference in the effect of giving compresses of boiled lemongrass water and red ginger water on decreasing pain scale in rheumatoid arthritis patients.This research method uses quantitative research, pre-experimental design using a two group pre-post-test design approach. The population in this study were all patients with rheumatoid arthritis at Simpur Bandar Lampung Health Center with a sample of 30 people. Data analysis using t test.The results of univariate analysis obtained that the average pain scale before being given a compress of warm lemongrass boiled water was 5.85, after being given a compress of warm lemongrass boiled water was 3.45. The average pain scale before being given a red ginger boiled water compress was 5.75, after being given red ginger boiled water was 2.65. The results of the bivariate analysis showed that there was a difference in the effect of giving lemongrass stem decoction compresses on the rheumatoid arthritis pain scale (p-value = 0.001). There is an effect of red ginger boiled water on the rheumatoid arthritis pain scale (p-value = 0.000). There is a difference between giving warm lemongrass boiled water compresses and red ginger boiled water compresses on the rheumatoid arthritis pain scale (p-value = 0.023).